Worker Protection Standard: Training Workers and Handlers - Frederick M. Fishel (EDIS, 2006)
The Worker Protection Standard (WPS) is a Federal regulation designed to protect agricultural workers (people involved in the production of agricultural plants) and pesticide handlers (people mixing, loading, or applying pesticides or doing other tasks involving direct contact with pesticides). It has been in full implementation since 1995. This document is PI-113, one of a series of the Pesticide Information Office, UF/IFAS Extension. Original publication date April 2006.